Electroacupuncture Stimulation at CV12 Inhibits Gastric Motility via TRPV1 Receptor. (9th September 2013) - Yu, Zhi; Cao, Xin; Xia, Youbing; Ren, Binbin; Feng, Hong; Wang, Yali; Jiang, Jingfeng; Xu, Bin
Abstract : Gastric dysmotility is one of the major pathophysiological factors in functional gastrointestinal disorders. Acupuncture, as one of the alternative approaches, is efficacious in the treatment of gastrointestinal motility disorders; however, the mechanism underlying its action is unclear. In the present study, we used both capsazepine, a TRPV1 antagonist, and TRPV1 knockout mice. Animals were divided into wild-type group (WT), capsazepine injection group (CZP, 0.5 mg/kg, i.p.), and TRPV1 knockout mice group (TRPV1 −/− ). Each of these three groups was divided into three subgroups, which were subjected to EA stimulation at acupoint Zhongwan (CV12) at a different intensity (1, 2, or 4 mA). We demonstrated that electroacupuncture at Zhongwan (CV12) markedly inhibited gastric motility at 2 and 4 mA in an intensity-dependent manner in wild-type mice. The inhibitory effect was also observed in capsazepine-injected and TRPV1 −/− mice but was no longer intensity dependent, indicating that TRPV1 is partially involved in the electroacupuncture-mediated modulation of gastric motility.